Larval chemosensory projections and invasion of adult afferents in the antennal lobe of Drosophila. - Tissot, M.; Gendre, N.; Hawken, A.; Stortkuhl, K.F.; Stocker, R.F. (Journal of Neurobiology, 1997)
We have studied the fate of olfactory afferents during metamorphic transformation of Drosophila melanogaster. Intracellular labeling of afferents from larval head chemosensilla suggests that the larval antennal lobe may be an olfactory target, whereas tritocerebral and suboesophageal centers are likely targets of gustatory sensilla. Application of monoclonal antibody 22C10 shows that the larval antennal nerve is the precursor of the adult antennal nerve and is used as a centripetal pathway for the adult afferents. Likely guidance cues are larval olfactory afferents that persist during early metamorphosis. P[GAL4] enhancer trap lines are introduced as efficient markers to follow the establishment of adult sensory projection. beta-Galactosidase and the bovine TAU protein were used as reporter proteins, and their expression patterns are compared. P[GAL4] lines MT14 and KL116 demonstrate that adult antennal afferents have arrived in the antennal lobe 24 h after pupariation and extend to the contralateral lobe 6 h later. Line MT14 expresses GAL4 mostly in basiconic sensilla and in certain trichoid sensilla, whereas KL116 is specific for trichoid and a small subset of basiconic sensilla. In the antennal lobe, largely complementary subsets of glomeruli are labeled by the two lines, in agreement with the observation that particular types of sensilla project to particular target glomeruli.